THE PRUDENTIAL EXCEPTION IN THE GATS AFTER THE CASE ARGENTINA – FINANCIAL SERVICES - Martins, Alexandre Marques da Silva (Revista de Direito Internacional e Globalização Econômica, 2018)
Experience has shown there has been a need for prudential measures to be imposed on financial services. The global financial crisis of 2007-08 is quite an emblematic example. Therefore, states and financial institutions have united to establish standards as for financial services like the Basel Committee. Only one case about prudential measures in the realm of financial services has been decided thus far at the WTO. In this case, adjudicators heavily utilized the recourse to the ordinary meaning of the main GATS expressions surrounding the prudential measures. This recourse may limit the aid that international norms other than the WTO legislation may provide when resolving issues related to the GATS prudential exception. Still according to the adjudicators, the prudential exception at issue is of evolutionary nature, evolving over time to adapt to particular situations. Besides, there has to be a rational relationship between the measures and their reasons.